Cx43 regulates mechanotransduction mechanisms in human preterm amniotic membrane defects - Costa, Eleni (2024)
Objective: The effects of mechanical stimulation in preterm amniotic membrane (AM) defects were explored. Methods: Preterm AM was collected from women undergoing planned preterm caesarean section (CS) due to fetal growth restriction or emergency CS after spontaneous preterm prelabour rupture of the membranes (sPPROM). AM explants near the cervix or placenta were subjected to trauma and/or mechanical stimulation with the Cx43 antisense. Markers for nuclear morphology (DAPI), myofibroblasts (αSMA), migration (Cx43), inflammation (PGE2) and repair (collagen, elastin and transforming growth factor β [TGFβ1]) were examined by confocal microscopy, second harmonic generation, qPCR and biochemical assays. Results: In preterm AM defects, myofibroblast nuclei were highly deformed and contractile and expressed αSMA and Cx43. Mechanical stimulation increased collagen fibre polarisation and the effects on matrix markers were dependent on tissue region, disease state, gestational age and the number of fetuses. PGE2 levels were broadly similar but reduced after co-treatment with Cx43 antisense in late sPPROM AM defects. TGFβ1 and Cx43 gene expression were significantly increased after trauma and mechanical stimulation but this response dependent on gestational age. Conclusion: Mechanical stimulation affects Cx43 signalling and cell/collagen mechanics in preterm AM defects. Establishing how Cx43 regulates mechanosignalling could be an approach to repair tissue integrity after trauma.